A first-in-human, phase 1a dose-escalation study of the selective MEK1/2 inhibitor FCN-159 in patients with advanced NRAS-mutant melanoma. (November 2022) - Mao, Lili; Guo, Jun; Zhu, Lingjun; Jiang, Yu; Yan, Wangjun; Zhang, Jian; Hui, Ai-Min; Yang, Yuchen; Diao, Lei; Tan, Yan; Zhao, Han; Jiang, Yiqian; et al.
Abstract: Background: A phase 1a first-in-human study evaluated the safety/tolerability, preliminary antitumour activity and pharmacokinetics of the oral MEK1/2 inhibitor FCN-159 in Chinese patients with advanced, NRAS -mutant melanoma. Patients and methods: Patients received a single FCN-159 dose at assigned levels, proceeding to continuous dosing (once daily [QD] for 28-day cycles) if no dose-limiting toxicities (DLTs) occurred within the next 3 days. Dose escalation was initiated after review of data for the previous dose level. The primary end-point was incidence of DLTs after the first dose. Results: Thirty-three patients were enrolled across nine FCN-159 dose groups (0.2–15 mg QD). One DLT occurred: grade 3 folliculitis in the 15-mg group. There was one grade >3 treatment-emergent adverse event (TEAE), death of unknown aetiology (not FCN-159 related). The most common FCN-159–related TEAE was rash (36.4%), and the incidence of grade ≥3 FCN-159–related TEAEs was 15.2%. Antitumour activity at QD doses <6 mg was limited; therefore, efficacy data are presented only for doses ≥6 mg (n = 21). The objective response and clinical benefit rates were 19.0% (four partial responses) and 52.4%, respectively. Median (95% confidence interval) duration of response and progression-free survival were 4.8 months (2.8–not reached) and 3.8 months (1.8–5.6), respectively. FCN-159 exposure increased dose-proportionately; geometric mean terminal half-life was 29.9–56.9 h. Conclusions: FCN-159 was well tolerated and demonstrated promising antitumour activity at doses ≥6 mg QD in patients with advanced, NRAS -mutant melanoma. The recommended phase 2 dose was 12 mg QD. ClinicalTrials.gov identifier: NCT03932253. https://clinicaltrials.gov/ct2/show/NCT03932253 . Highlights: There is currently no standard targeted therapy for advanced NRAS mut melanoma. FCN-159, a selective MEK1/2 inhibitor, was evaluated in a first-in-human study. FCN-159 was well tolerated in Chinese patients with advanced NRAS mut melanoma. Preliminary signs of antitumour activity were observed at FCN-159 doses ≥6 mg QD. The findings support further study of FCN-159 in patients with NRAS mut melanoma.